Large increase in the energy product of Fe3Se4 by Fe-site doping - Sen Bishwas, Mousumi; Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Fe3Se4 possesses a large coercivity at room temperature. At lower temperature, a coercivity value up to 40 kOe has been achieved. However, due to a relatively lower saturation magnetization value, the energy product of this material is not suitable for its use as rare-earth-free hard magnetic material. Although the anisotropy and magnetic structure of Fe3Se4 have been topics of research, there is no attempt to increase the energy product. Here, we report the synthesis of Fe3-xMnxSe4 (x = 0.01-0.2) nanorods. As required for practical applications, after doping, the Curie temperature remains unchanged; however, at optimum (x = 0.03) doping of manganese ions, the magnetization of the host matrix increases significantly from 4.84 to 7.54 emu/g. The corresponding energy product value was found to be increased by more than 130%. At low temperature (10 K) the energy product shows almost a 2 order of magnitude increase (similar to 0.12 MG Oe), which makes it valuable for many low temperature applications. This improvement is a vital step for its use in some of the household applications where a large volume and relatively lower energy product are needed.

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic

Ln(8) (Ln = Gd, Ho, Er, Yb) Butterfly core-exhibiting magnetocaloric effect and field-induced SMM behavior for Er analouge - Bala, Sukhen; Adhikary, Amit; Bhattacharya, Sudeshna; Sen Bishwas, Mousumi; Poddar, Pankaj; Mondal, Raju (ChemistrySelect, 2017)
In this article, we report four pyridyl-pyrazolyl based poly-nuclear cluster complexes with Ln(8) {Ln = [Gd-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(2)(MeOH)(1), [Ho-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](2), [Er-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(H2O)(3), [Yb-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(4) [DEA = Diethanolamine] cores. The impetus for this study was to explore the magnetic behaviour of lanthanide ions which are often ignored or overlooked. X-ray crystal analysis show that these complexes are isostructural and exhibit an interesting butterfly like topology. The semi-rigidity and asymmetric nature of the ligand led to different coordination environment around the metal centres. The lanthanide ions adopt two types of geometry, a bicapped trigonal prism and a distorted square antiprismatic geometry around the metal center. Such dissimilar coordination environments around the lanthanide centre can have profound effects on their magnetic behaviour. Indeed, the magnetic measurements revealed significant magnetocaloric effect for octanuclear gadolinium complex 1 with magnetic entropy change (-Delta S-m ) of 31.4 J kg(-1) K-1 for Delta H = 9 T at T = 3 K whereas Er analogue complex 3 displayed SMM behavior.

Luminescence turn-off detection of metal ions and explosives using graphene quantum dots - Jyotsna, Shubhra; Sadhu, Subha; Sharma, Vinay; Gupta, Preeti; Sharma, Geeta; Poddar, Pankaj (MRS Communications, 2022)
Green luminescent graphene quantum dots (GQDs) obtained from combustion of white printing paper were used for detection of fourteen different metal ions and six different explosives in an aqueous medium. These were obtained using a microwave-assisted synthesis process. After optimizing the experimental conditions (pH 6; quantum yield (QY) similar to 38.2%), a sensitive sensing system was developed to detect explosives and free residual metal ions in the environment based on fluorescence quenching of GQDs. The as-synthesized GQDs, as a sensing system, is most sensitive for Cu2+ ion and 2,4-DNP with a detection limit of 0.62 mu M and 0.50 mu M, respectively.